Is chytridiomycosis driving Darwin's frogs to extinction? - Claudio Soto-Azat (Public Library of Science (PLoS), 2013)
Darwin's frogs (Rhinoderma darwinii and R. rufum) are two species of mouth brooding frogs from Chile and Argentina that have experienced marked population declines. Rhinoderma rufum has not been found in the wild since 1980. We investigated historical and current evidence of Batrachochytrium dendrobatidis (Bd) infection in Rhinoderma spp. to determine whether chytridiomycosis is implicated in the population declines of these species. Archived and live specimens of Rhinoderma spp., sympatric amphibians and amphibians at sites where Rhinoderma sp. had recently gone extinct were examined for Bd infection using quantitative real-time PCR. Six (0.9%) of 662 archived anurans tested positive for Bd (4/289 R. darwinii; 1/266 R. rufum and 1/107 other anurans), all of which had been collected between 1970 and 1978. An overall Bd-infection prevalence of 12.5% was obtained from 797 swabs taken from 369 extant individuals of R. darwinii and 428 individuals representing 18 other species of anurans found at sites with current and recent presence of the two Rhinoderma species. In extant R. darwinii, Bd-infection prevalence (1.9%) was significantly lower than that found in other anurans (7.3%). The prevalence of infection (30%) in other amphibian species was significantly higher in sites where either Rhinoderma spp. had become extinct or was experiencing severe population declines than in sites where there had been no apparent decline (3.0%; x(2) = 106.407, P<0.001). This is the first report of widespread Bd presence in Chile and our results are consistent with Rhinoderma spp. declines being due to Bd infection, although additional field and laboratory investigations are required to investigate this further.